Robert of Anjou in the Death Glory: The ‘Saint Louis of Toulouse’ of Simone Martini - Vagnoni, Mirko (Eikón / Imago, 2021)
This paper aims to analyse the iconographic meaning of the renowned Simone Martini’s altarpiece ‘Saint Louis of Toulouse crowns king Robert of Anjou’ (1317-1319), currently preserved in the Museo di Capodimonte in Naples. Historiography has generally interpreted its main scene as a representation of Louis’s abdication to the royal title and the consequent Robert’s coronation as King of Naples. In particular, this artifact has been considered the result of a real political communication strategy staged by the King of Naples in order to legitimize his disputed succession to the throne. Conversely, following an interpretation that frames the altarpiece in its context of use and fruition and puts emphasis on its specific function, this text proposes to interpret the meaning of this artwork in connection with the role of intercessor with God in favor of the souls of the members of the Angevin house attributed to Saint Louis. In this direction, it represents, in a purely religious meaning, Robert of Anjou dead while he is receiving the crown of the Eternal Life in the Kingdom of Heaven.